Предмет: Алгебра,
автор: leonardo5113
найдите значение выражения
(7,6*10^-3)(7*10^-3)
Ответы
Автор ответа:
0
7,6*7*10^(-3-3) = 7,6*7*10^( - 6) = 53,2 * 10^(-6)= 0,0000532
Автор ответа:
0
(7,6*10^-3)(7*10^-3)=
=(7.6 * (1/10³))*(7 * (1/10³))=
=(7.6 * (1/1000))*(7 * (1/1000))=
=(7.6*0.001) * (7/100)=
=0.0076 * 0.007 =
=0.0000532
=(7.6 * (1/10³))*(7 * (1/10³))=
=(7.6 * (1/1000))*(7 * (1/1000))=
=(7.6*0.001) * (7/100)=
=0.0076 * 0.007 =
=0.0000532
Похожие вопросы
Предмет: Алгебра,
автор: Hamachik
Предмет: История,
автор: hibicheeees
Предмет: Алгебра,
автор: rorukl
Предмет: Математика,
автор: диана291012
Предмет: Математика,
автор: ArinaTrepyshko